Pidgin and Hawai‘i English: An overview - Drager, Katie (International Journal of Language, Translation and Intercultural Communication, 2012)
Today, most people from Hawai‘i speak Pidgin, Hawai‘i English, or both. This paper presents a brief discussion of the history of both the creole (called Pidgin or Hawaii Creole) and the variety of English spoken in Hawai‘i referred to as Hawai‘i English. The creation of Pidgin and the prevalence of English in Hawai‘i have a complex history closely tied with various sociohistorical events in the islands, and the social hegemony established during the plantation days still persists today. While Pidgin is stigmatized and is deemed inappropriate for use in formal domains, it has important social functions, and the infl uence from diff erent languages is viewed as representative of the ethnic diversity found in the islands. This paper treats Pidgin and Hawaii English as independent from one another while commenting on some of the linguistic forms that are found in both. Lexical items, phonological forms,and syntactic structures of Pidgin and Hawai‘i English are presented alongside a discussion of language attitudes and ideologies. Recent work that attempts to address the negative attitudes toward Pidgin is also discussed.